An Analysis upon Different Accounting Practices of SMEs and It’s Influences on Usage of Financing: The Impact of Accounting Practices on Financing for SMEs (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study seeks to examine the accounting practice of small and medium sized enterprises and its effect on access to finance. It identifies the sector as the key to unlocking the economic potentials of the country. However, the sector is constrained by a number of factors which include among others minimum or poor accounting practice and difficulty in accessing credit facilities.The study revealed that the majority of the studied firm has no formal accounting practice. The study also revealed that the major sources of finance available for the establishment and expansion of SMEs are personal saving, micro finance, money from friends or relative, iqub and less from banks. The result of ordinary least square regression evidences that variables such as capital, manager education level and age of the firms are the significant determinants of firms’ accounting practices whereas the problems significantly associated with access to bank credits are the demand for collateral, accounting practice or formal accounting information and age of the firm.